2015
DOI: 10.1001/jamapediatrics.2015.0418
|View full text |Cite
|
Sign up to set email alerts
|

Adverse Events After Routine Immunization of Extremely Low-Birth-Weight Infants

Abstract: Importance Immunization of extremely low-birth-weight (ELBW) infants in the neonatal intensive care unit (NICU) is associated with adverse events, including fever and apnea or bradycardia, in the immediate postimmunization period. These adverse events present a diagnostic dilemma for physicians, leading to the potential for immunization delay and sepsis evaluations.Objective To compare the incidence of sepsis evaluations, need for increased respiratory support, intubation, seizures, and death among immunized E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
21
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 22 publications
1
21
0
2
Order By: Relevance
“…This potential for selection bias has been previously described in the literature. 17 The infants who are transferred to our level 4 NICU often represent the sickest and most fragile patients; although we propose that these infants are likely to be at least as ill as those found in other NICUs, it is not possible to assess this confounder. An additional limitation is the data abstraction from health care providers' documentation.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…This potential for selection bias has been previously described in the literature. 17 The infants who are transferred to our level 4 NICU often represent the sickest and most fragile patients; although we propose that these infants are likely to be at least as ill as those found in other NICUs, it is not possible to assess this confounder. An additional limitation is the data abstraction from health care providers' documentation.…”
Section: Discussionmentioning
confidence: 94%
“…Previous studies have evaluated apnea, bradycardia, and desaturation (A/B/D) episodes after immunization of preterm infants with mixed results. [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] Infants with bronchopulmonary dysplasia (BPD) are often considered to be at highest risk of adverse events after immunization 24 ; however, this population is known to be at highest risk of severe complications from developing vaccine-preventable illnesses. 4,5,9,26 The objectives of this study were to determine if infants with BPD experience respiratory decompensation after immunization in greater proportion than those infants without BPD and to explore patient characteristics that may predispose infants to respiratory decompensation after immunization.…”
mentioning
confidence: 99%
“…With the unique nature of patients with CLD and repeated clinician concerns (whether real, perceived, or unknown) for clinical instability after immunization, it was necessary to agree on a set of exclusion criteria for allowing immunization delay in this population (infants not eligible for immunization during the scheduled time). Via consensus, attending neonatologists on the CLD team established the following exclusion criteria: (1) a fraction of inspired oxygen (FIO 2 ) requirement of .80%, (2) pulmonary hypertensive crisis, (3) positive blood culture results or if within 48 hours of a sepsis evaluation, (4) if within 5 days of a surgical or interventional procedure, (5) receiving steroid treatment (not including a physiologic hydrocortisone dose for adrenal insufficiency), (6) a CLD team consensus of contraindication, and (7) parental refusal. Each week, during team rounds, the CLD team discussed the eligibility for immunization of each CLD patient according to these predefined criteria.…”
Section: Methodsmentioning
confidence: 99%
“…Some studies suggest that immunization has been associated with an increased risk of sepsis evaluations, a need for increased respiratory support, and unplanned intubation in infants with very low birth weight. 5 However, 1 study revealed that preterm infants who received the diphtheriatetanus-acellular pertussis vaccine at 2 months after birth are no more likely to experience prolonged apnea and bradycardia than control infants. 6 Another retrospective cohort study of premature infants ,32 weeks' gestational age revealed that respiratory decompensation requiring clinical intervention after immunizations in infants with BPD is uncommon and comparable with that in infants without BPD.…”
mentioning
confidence: 99%
“…НСясным остаСтся вопрос ΠΎΠ± эффСктивности ΠΈΠΌ-ΠΌΡƒΠ½Π½ΠΎΠ³ΠΎ рСагирования ΠΈ Ρ€Π°Π·Π²ΠΈΡ‚ΠΈΠΈ Π½Π΅ΠΆΠ΅Π»Π°Ρ‚Π΅Π»ΡŒΠ½Ρ‹Ρ… Ρ€Π΅Π°ΠΊΡ†ΠΈΠΉ Π½Π° Π²Π°ΠΊΡ†ΠΈΠ½Π°Ρ†ΠΈΡŽ Ρƒ Π³Π»ΡƒΠ±ΠΎΠΊΠΎΠ½Π΅Π΄ΠΎΠ½ΠΎΡˆΠ΅Π½Π½Ρ‹Ρ… Π½ΠΎΠ²ΠΎΡ€ΠΎΠΆΠ΄Π΅Π½Π½Ρ‹Ρ… [12].…”
unclassified